THU0079 Polypharmacy, Although not Combination Dmard Therapy, in Rheumatoid Arthritis is Associated with Increased Hospitalisation Risk. (9th June 2015) - Filkova, M.; Ibrahim, F.; Norton, S.; Scott, D.; Mant, T.; Cope, A.; Molokhia, M.; Galloway, J.
Abstract : Background: Multimorbidity is a major problem in rheumatoid arthritis (RA) but is difficult to measure. Polypharmacy - co-prescribing an individual multiple medications – is a surrogate marker for the burden of multimorbidity. We evaluated the inter-relationships between polypharmacy, disease activity, disability and acute hospital admission in a retrospective cohort study of RA patients managed at one large UK specialist centre. Our hypothesis was that polypharmacy would associated with uncontrolled RA, disability and acute hospital admission. Methods: Routinely captured data from a UK teaching hospital were retrospectively analysed. An 18-month period of observation (May 2013 - Nov 2014) was chosen for analysis. All patients registered with a consultant diagnosis of RA at the start of follow up were included. Patients were stratified according to levels of polypharmacy. Cox proportional hazards were used to study risk of hospitalization in each stratum. Follow up was censored at date of first admission or study end, whichever came first. A restricted cubic spline model compared hospitalisation risk with number of prescribed medications. Further analysis explored relationships between DMARD prescribing and hospitalisation risk. Results: 1, 101 RA patients were studied; their baseline features are shown in the table. The mean number of medications was 5: 60% were on ≤5, 29% on 6-9 and 11% on ≥10 medications. Polypharmacy correlated with increasing age and longer disease durations (Table ). Polypharmacy was associated with higher DAS28 and higher HAQ scores (Table ). Increasing polypharmacy was associated with more frequent acute hospitalisations; there was a marked non-linear increase in risk in patients taking ≥10 medications. Patients in the highest polypharmacy strata (≥10) had an age and gender adjusted hazard ratio for hospitalisation of 3.1 (95% CI 2.1, 4.5) compared to those in the lowest strata (0-5). Different DMARD prescription strategies were not significantly associated with hospitalisation risk; but patients receiving triple DMARD therapy had lower hospitalisation risks than those on mono therapy, though this risk reduction did not achieve statistical significance in this group. Finally steroid use resulted in doubling the adjusted risk of hospitalisation. Conclusions: Polypharmacy is common in RA patients and it is a poor prognostic marker. When patients are receiving ≥10 medications they have higher DAS28 scores, worse disability and substantially greater risks of acute hospitalisation. There are two likely drivers for these effects. Firstly, polypharmacy indicates greater comorbidity burdens. Secondly, polypharmacy increases the risk of drug-related toxicity. Not all polypharmacy is negative; using triple DMARDs may be beneficial. The negative impacts of polypharmacy across all impacts of RA outcomes suggests the need for rheumatology specialists to have greater input to the overall integrated management of RA patients problems rather than confining their input to rheumatological aspects of care. Disclosure of Interest: None declared